Resource utilisation and curriculum implementation in community colleges in Kenya - Peter Changilwa Kigwilu; Winston Jumba Akala (International Journal for Research in Vocational Education and Training (IJRVET), 2017)
The study investigated how Catholic-sponsored community colleges in Nairobi utilise the existing physical facilities and teaching and learning resources for effective implementation of Artisan and Craft curricula. The study adopted a mixed methods research design. Proportional stratified random sampling was used to sample 172 students and 18 teachers while four directors of community colleges were purposively selected. Questionnaires were administered to students and teachers, while directors were interviewed. Teaching and learning resources, such as workshops, equipment, lecture rooms, laboratories, raw materials for practical training and reference books, were found to be adequate, although underutilised. However, sports grounds, libraries and course texts were inadequate. Resource inadequacies were often mitigated by signing equipment co-sharing agreements with peer institutions and local firms. Teachers rated highly the influence of physical facilities on curriculum implementation. Both students and teachers rated highly the influence of teaching and learning resources on curriculum implementation. The study concludes that, while some physical facilities and teaching and learning resources are adequate, their underutilisation and the inadequacy of other core facilities and resources, such as libraries and course textbooks, hinder effective teaching and learning in these community colleges.
Keywords: 330; VET; Vocational Education and Training; Artisan and Craft; Community Colleges; Curriculum Implementation; Resource Utilisation